SİMİLARİTİES OF AİR CRAFT CRASHED İN CYPRUS BETWEEN YEARS İN 1973-1988 - Izzet Derkan (International Journal of Research Science and Management, 2016)
This article is about aircraft crashed happened in 1973 and 1988. In this article aircrafts crashed were examined in those years. The first aircraft crash in this artice was happened in 1973 under poor visibility and the other was happened in 1988 under clear weather conditions.